Landscaping and sustainability for the promotion os community well-being - Trescastro Pacheco, Fernanda; Sponchiado, Margarete (Guará Journal, 2016)
The extension project of University of the State Rio Grande do Sul (UERGS) was a practice of interdisciplinary and contributed to environmental management in the city of Tapes, southern Brazil. In this context, the aim of the project was recreated a landscaped environment with fruit trees, medicinal native and exotic decorative plants. The soil structure studies with practices such as planting species that contribute to their recovery, recycling and reuse fines with community participation. How methodologies were carried out theoretical and practical workshops totaling 40 hours in the afternoon, where the target audience is the local community, teachers, students from local schools and academics from UERGS. The workshops allowed the exchange of knowledge, as well as soil conservation challenge, species of local vegetation and unfunded. Landscaping techniques and ecodesign have been applied with the use of visual aids and presentation videos. The planning and implementation of landscaped space was developed with participants who performed management activities and multiplication of plants, soil management, site area of measuring the project, survey of existing plants and study forms. The project aroused and made possible the observation of different environments, encouraged teamwork, promoted participation in actions that contributed to make dynamic and interactive spaces. The workshops resulted, in the formation of new noticeably space pleasant, making multipliers participants in actions for the welfare of the community.